Capitalization of tires waste as derived fuel for sustainable cement production - Vasiliu, Leonid; Gençel, Osman Serden; Damian, Ioan; Harja, Maria (Elsevier Ltd, 2023)
The co-incineration of tires waste is inexpensive; the questions are referring to the influence over clinker quality and gaseous emissions. The use of tires waste as a waste-derived fuel imposes more researches to establish influence over process parameters, technological availability, costs, kiln design for processing different type of fuels, quality and homogeneity of alternative fuels, the caloric value, quality of clinker, gaseous emission, etc. The data was obtained at an industrial scale, during two periods when 11% tires waste replaces coal, with or without raw mill in function. The results were compared with the period when coal was the only fuel used. The principal objective of this paper is to establish the influence, at the industrial scale, of the use of tires waste on: the technological parameters of the clinker kiln as well as on its energy efficiency and stability; the effects of tires waste incineration on clinker process and properties of clinker, SO2, NOx and heavy metals emission. The experimental results presented in the paper demonstrated that the co-incineration of tires wastes in cement plants have the multiple benefits: save raw materials, reduced CO2 emission, thermo-energy recovery of waste with rich energy content, reduces waste disposal, etc. © 2023 Elsevier B.V., All rights reserved.
Keywords: Alternative Fuels; Cement Production; Emission; Energy; Kiln Stability; Tires Waste